2000
DOI: 10.4049/jimmunol.164.12.6480
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells Cause Liver Injury and Facilitate the Induction of T Cell-Mediated Immunity to a Viral Liver Infection

Abstract: NK cells are a relatively rare cell population in peripheral lymphoid organs but are abundant in the liver, raising questions as to their function in immune responses to infections of this organ. To investigate this, cell-mediated immunity to viral liver infection induced by a type 5, replication-defective, adenovirus was examined. It is shown that NK cells in the absence of T cells cause hepatocyte apoptosis in virus-infected livers associated with an increase in liver enzymes in the serum. Concomitantly, NK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(140 citation statements)
references
References 42 publications
5
133
0
2
Order By: Relevance
“…Again, in the mouse model during the acute phase of LCMV infection, NK cells increase in the peripheral blood by 10% over three days and NK cell margination results in a > 30% increase in the liver (McIntyre & Welsh 1986. Murine NK cells have been pheno typically characterised as NK 1.1 + TCR -, CD3 -, CD8 + , asialo + and CD16 + ; they are known to stimulate the induction of T cell-mediated immunity by secreting IFN-γ and they also cause some cell death in the liver (Liu et al 2000). In our monkey study, where NK cells are primarily CD3 -CD16 + , we did not investigate the migration of NK cells to peripheral organs, but in other published studies, we have demonstrated the presence of unidentified cellular infiltrates in the liver and lymphoid tissues (Lukashevich et al 2002(Lukashevich et al , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Again, in the mouse model during the acute phase of LCMV infection, NK cells increase in the peripheral blood by 10% over three days and NK cell margination results in a > 30% increase in the liver (McIntyre & Welsh 1986. Murine NK cells have been pheno typically characterised as NK 1.1 + TCR -, CD3 -, CD8 + , asialo + and CD16 + ; they are known to stimulate the induction of T cell-mediated immunity by secreting IFN-γ and they also cause some cell death in the liver (Liu et al 2000). In our monkey study, where NK cells are primarily CD3 -CD16 + , we did not investigate the migration of NK cells to peripheral organs, but in other published studies, we have demonstrated the presence of unidentified cellular infiltrates in the liver and lymphoid tissues (Lukashevich et al 2002(Lukashevich et al , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Activated hepatic NK cells are able to kill hepatocytes and induce liver injury such as viral liver infection (adenovirus), Pseudomonas aeruginosa exotoxin A (PEA) injection and carrageenan administration [9][10][11], and polyinosinic:polycytidylic acid [Poly(I:C)] injection as reported by Makoto Ochi et al and us [12,13]. Mole-cules including IFN-c, IL-12, Perforin and TRAIL contributed to NK cell cytotoxicity against hepatocytes [9,[11][12][13]. Furthermore, pre-activated T cells by a low dose of ConA could enhance the ability of Poly(I:C)-activated NK cells to cause more severe hepatocyte injury [14].…”
Section: Introductionmentioning
confidence: 99%
“…70 IFN-␥ production by these cells not only has antiviral effects but also mediates the intrahepatic recruitment of inflammatory cells. 71,72 Direct evidence of the activation state of NK and NK-T cells during the initial phase of HCV infection is lacking. Nevertheless, the absence of signs of liver inflammation in the first 4 to 6 weeks after HCV infection 10,38,41,44,63 suggests that the contribution of NK and/or NK-T cells in this early phase may be minimal.…”
Section: The Innate Immune Response In Hcv and Hbv Infectionsmentioning
confidence: 99%